Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 530 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Chiroptera", "HasGeospatialIssue is false", "HasCoordinate is true", { "or" : [ "TypeStatus is Exparatype", "TypeStatus is Plastolectotype", "TypeStatus is Supplementary type", "TypeStatus is Lectotype", "TypeStatus is Epitype", "TypeStatus is Topotype", "TypeStatus is Isosyntype", "TypeStatus is Praneotype", "TypeStatus is Isolectotype", "TypeStatus is Plastotype", "TypeStatus is Plastoneotype", "TypeStatus is Extype", "TypeStatus is Notatype", "TypeStatus is Plastoholotype", "TypeStatus is Exholotype", "TypeStatus is Alloneotype", "TypeStatus is Holotype", "TypeStatus is Syntype", "TypeStatus is Isotype", "TypeStatus is Neotype", "TypeStatus is Allolectotype", "TypeStatus is Hapantotype", "TypeStatus is Plastoisotype", "TypeStatus is Allotype", "TypeStatus is Exsyntype", "TypeStatus is Original material", "TypeStatus is Exneotype", "TypeStatus is Paratype", "TypeStatus is Plastosyntype", "TypeStatus is Iconotype", "TypeStatus is Plastoparatype", "TypeStatus is Isoneotype", "TypeStatus is Exhisotype", "TypeStatus is Paralectotype", "TypeStatus is Exepitype", "TypeStatus is Exlectotype", "TypeStatus is Cotype", "TypeStatus is Secondary type" ] } ] } The dataset includes 530 records from 16 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0007774-160623103540712/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences